Improving thermal comfort and energy saving in buildings using advanced optimal configuration approaches for heating structures and panels (Architecture Image Studies, 2024)
The study aims to address advanced approaches to the optimal settings of heating structures and panels to improve thermal comfort and energy efficiency in buildings. The study analysed various materials for thermal insulation, different heating systems and energy-efficient windows, using common formulas to calculate their thermal performance and efficiency. The study analysed various modern methods of optimising heating systems to improve thermal comfort and energy efficiency in buildings. As such, the study determined that the use of intelligent heating control systems, such as smart thermostats and sensors, can significantly reduce energy consumption. The study also determined that heat pumps, especially geothermal and air source heat pumps, are effective solutions for sustainable heating. The study results confirmed that three-chamber windows with a third gap between the glass panes can maximise energy savings by significantly reducing heat loss and providing high thermal insulation. The study also determined that condensing gas boilers and heat pumps are optimal for efficient energy savings. Low-temperature heating systems, such as underfloor heating and efficient radiators, contribute to even heat distribution and energy savings. The use of renewable energy sources, such as solar collectors and wind turbines, was also determined to be an effective means of reducing dependence on traditional energy resources. The study also showed that the integration of various technologies and systems into a single climate control system allows for maximum efficiency and comfort. As a result, the combined use of innovative methods and materials not only significantly reduces energy consumption but also improves living conditions in modern buildings.